Pharmacy students' inter-professional perceptions towards the pharmacy profession in Malaysia / Firas Afiqah Nor Azizi - Nor Azizi, Firas Afiqah (2015)
Interprofessional in term of the health care system is said as a group of people such as doctors, nurses and pharmacists that have different backgrounds in practical training, but work together in one organization to achieve one ultimate goal which is to effectively serve the community. The aim of this study is to investigate the perceptions of pharmacy students in Universiti Teknologi MARA (UiTM) towards interprofessional in the pharmacy profession in Malaysia by distributing questionnaire that consists of two sections, demographic section and the survey on the perception of pharmacy students regarding the interprofessional collaboration in a health care team to the first, second, third and final year students of faculty pharmacy in UiTM. The majority of the respondents were female (n = 253, 92.0%) while only 8.0% from the male students (n = 22). The result shown that there was no significant difference in the interprofessional perception between the variable groups except for the academic year (p = 0.000), hospital or community pharmacy training (p = 0.003) and attendance to a seminar OJ conference (p = 0.045) within the last six months. Third year students have better thought on the importance of professional cooperation between health care students. Fourth year students have the highest score compared to other study years on perception of actual cooperation resource sharing within and across professions. In a conclusion. fourth and third year students have better perception towards interprofessional collaboration between health care professionals. Hospital or community training, attendance to pharmacy seminar and conference greatly affect the attitude of students towards interprofessional collaboration.